Design and Development Application to Manage Pujasera 16 - Haris Imansya; Sri Hariani Eko Wulandari; Ignatius Adrian Mastan (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Pujasera Enam Belas make serious efforts to give the best service to consumer and outlet owners to increase revenue of the Pujasera. The main problem is process of ordering food is on each of outlets and the payment is also paid by consumer in each outlet. This could make manipulation of finance from the outlet employee. Sales recap which take a long time. And also with conventional method could make mistake in calculation of revenue sharing. Because of the problems listed above, an application which can solve all that problem is needed. Based on the problems, the solution was made are to design and make an application which could manage pujasera with centered cashier system. The application could record the cooperation between outlet owner and head of pujasera, like the sum of omset. The owner of outlet would not be bothered with order transaction and payment, so the owner could focus to serve the food. Result from testing shows that the application could help in managing process of Pujasera Enam Belas, which are: granted user access, employee registration, rent registration, outlet registration, outlet contract payment, selling transaction, sale report making, sale outlet report, and so on.